Applying 5E teaching model in recognizing regular polygons and rotations with the help of GeoGebra software - Nguyen, Ngoc-Giang (Advances in Social Sciences Research Journal, 2021)
The 5E teaching model is a teaching model that gives students positive motivation. The 5E teaching model was proposed by Rodger W. Bybee and colleagues while working in the educational organization "Research on the curriculum framework for biology" in Colorado, the USA in 1987. The model is built based on the constructivist theory of learning, knowledge is formed through the experience and practice of learners. 5E stands for 5 words: Engagement - Exploration - Explanation - Elaboration - Evaluation, representing the five steps of the 5E teaching process. Our study aims to apply the 5E teaching model in regular polygon recognition and rotation with the help of GeoGebra software. With the theoretical research method and the experimental method for 102 students, including 52 students in the experimental class and 50 students in the control class, the study has shown that students who learn according to the 5E teaching model have better results than students who do not study this model. In addition, the research results also show that the 5E teaching model with the support of GeoGebra software in teaching regular polygon and rotation recognition has many advantages, developing learners' capacity and quality. Learners show much more interest and excitement than traditional teaching. Students develop their self-study and self-discovery abilities. The findings from the research results applying the 5E model are of great significance to teaching today.